Analysis of the Influence of Green Supply Chain Management on the Environmental and Financial Performance of MSMEs - Chanif Kurnia Sari; Dian Kusumaningrum (Journal of Social Science and Humanities, 2026)
Escalating global environmental concerns compel the business sector, including Micro, Small, and Medium Enterprises (MSMEs), to embrace sustainable operational practices. This study examines the influence of Green Supply Chain Management (GSCM) on environmental performance and financial performance in culinary MSMEs located in Ngebel Village, Ponorogo Regency, East Java, Indonesia. GSCM is operationalized through four dimensions: green purchasing, green manufacturing, green distribution, and reverse logistics. A quantitative survey design was employed, with data collected via structured questionnaires administered to 20 MSME owners or managers. Structural Equation Modeling based on Partial Least Squares (SEM-PLS) was utilized for analysis. Results indicate that all GSCM dimensions exert a positive and statistically significant effect on environmental performance (R² = 0.612), with green manufacturing emerging as the dominant predictor (β = 0.436, p < 0.001). GSCM dimensions also significantly influence financial performance (R² = 0.482), with green manufacturing again proving most influential (β = 0.369, p = 0.001). Environmental performance further functions as a mediating pathway between GSCM and long-term financial gains. Despite initial investment requirements, resource efficiency improvements and enhanced brand reputation were found to sustainably augment MSME profitability. The findings provide practical guidance for MSME practitioners and policymakers seeking to integrate green practices as a competitive strategy within Indonesia's developing economy context.